First Activation of the WHO Emergency Medical Team Minimum Data Set in the 2019 Response to Tropical Cyclone Idai in Mozambique. Issue 6 (3rd December 2022) - Kubo, Tatsuhiko; Chimed-Ochir, Odgerel; Cossa, Matchecane; Ussene, Isse; Toyokuni, Yoshiki; Yumiya, Yui; Kayano, Ryoma; Salio, Flavio
Abstract: Introduction: During a disaster, comprehensive, accurate, timely, and standardized health data collection is needed to improve patient care and support effective responses. In 2017, the World Health Organization (WHO) developed the Emergency Medical Team (EMT) Minimum Data Set (MDS) as an international standard for data collection in the context of disasters and public health emergencies. The EMT MDS was formally activated for the first time in 2019 during the response to Cyclone Idai in Mozambique. Study Objective: The aim of this study was to analyze data collected through the EMT MDS during Cyclone Idai of 2019 and to identify the benefits of and opportunities for its future use. Methods: The EMT MDS was used for data collection. All 13 international EMTs deployed from March 27 through July 12 reported data in accordance with the EMT MDS form. The collected data were analyzed descriptively. Results: A total of 18, 468 consultations, including delivery of 94 live births, were recorded. For children under-five and those five-years and older, the top five reasons for consultation were minor injuries (4.5% and 10.8%, respectively), acute respiratory infections ([ARI] 12.6% and 4.8%, respectively), acute watery diarrhea (18.7% and 7.7%, respectively), malaria (9.2% and 6.1%, respectively), and skin diseases (5.1% and 3.1%, respectively). Non-disaster-related health events accounted for 84.7% of the total health problems recorded. Obstetric care was among the core services provided by EMTs during the response. Conclusion: Despite of challenges, the EMT MDS reporting system was found to support the responses and coordination of EMTs. The role of the Mozambican Ministry of Health (MOH), its cooperation with EMTs, and the dedicated technical support of international organizations enabled its successful implementation.